Androgen-Induced Immunosuppression - Gubbels Bupp, Melanie R.; Jorgensen, Trine N. (Frontiers in Immunology, 2018)
In addition to determining biological sex, sex hormones are known to influence health and disease via regulation of immune cell activities and modulation of target-organ susceptibility to immune-mediated damage. Systemic autoimmune disorders such as systemic lupus erythematosus, rheumatoid arthritis and multiple sclerosis are more prevalent in females, while cancer shows the opposite pattern. Sex hormones have been repeatedly suggested to play a part in these biases. In this review, we will discuss how androgens and the expression of functional androgen receptor (AR) affect immune cells and how this may dampen or alter immune-response(s) and affect autoimmune disease incidences and progression.